DOP79 Effect of vedolizumab on surgical rates in IBD: post hoc analysis from the GEMINI trials. (25th January 2019) - Feagan, B G; Sands, B E; Lirio, R; Lissoos, T; Wang, J; Feng, D; Lasch, K
Abstract: Background: Vedolizumab (VDZ) is a safe and effective treatment for moderately to severely active ulcerative colitis (UC) and Crohn's disease (CD); however, effects on surgical rates have not yet been evaluated. This study aimed (1) to compare the surgical incidence rates of VDZ and placebo (PLA) in GEMINI I (UC; NCT00783718) and II (CD; NCT00783692); and (2) to describe the surgical incidence rates through year 5 from the GEMINI LTS trial (UC and CD; NCT00790933). Methods: Data were pooled from Week 6 induction VDZ responders who were randomised to VDZ or PLA maintenance (intent-to-treat [ITT] maintenance populations) from GEMINI I 1 and II, 2 and from patients receiving VDZ in the GEMINI LTS trial. 3, 4 Using the Kaplan–Meier product-limit method, we estimated 'time to first surgery' through 1 year (VDZ and PLA groups from GEMINI I and II) and 5 years (VDZ1 and VDZ2 groups from GEMINI LTS. VDZ1 = VDZ throughout; VDZ2 = PLA from Week 6 to 1 year, then VDZ for the LTS study). Patients without surgery were censored at the last follow-up date through 1 year and 5 years. The log-rank test was used for comparisons between groups. Results: The analysis included 834 patients in total. Mean ages were 40.0 and 35.7 years for patients with UC and CD, respectively; proportions of prior tumour necrosis factor antagonist failure were 39.9 and 54.9%, and mean disease duration times were 7.2 and 8.6 years. Figure 1 shows cumulative surgical incidence rates for the study groups, and the log-rank comparisons at 1 year (VDZ and PLA groups) and 5 years (VDZ1 and VDZ2 groups). Conclusions: In this population of patients with moderately to severely active UC or CD, surgery rates within the first year of observation were lower in patients assigned to VDZ than those who received PLA with a significant difference observed in UC. For patients who continued treatment for up to 5 years, VDZ provided long-term benefit in both diseases with low rates of surgical intervention. The post hoc nature of the analysis and the small number of surgical events require further real-world evaluation of the ability of VDZ to reduce surgical rates in patients with UC and CD. References 1. Feagan BG, Rutgeerts P, Sands BE et al . Vedolizumab as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2013;369:699–710. 2. Sandborn WJ, Feagan BG, Rutgeerts P, et al . Vedolizumab as induction and maintenance therapy for Crohn's disease. N Engl J Med 2013;369:711–21. 3. Loftus EV Jr, Colombel JF, Feagan BG, et al. Long-term efficacy of vedolizumab for ulcerative colitis. J Crohns Colitis 2017;11:400–11. 4. Vermeire S, Loftus EV Jr, Colombel JF, et al. Long-term efficacy of vedolizumab for Crohn's disease. J Crohns Colitis 2017;11:412–24.